Sexual and reproductive health-related knowledge, attitudes and support network of Italian adolescents - Laura Brunelli; Giulia Bravo; Federico Romanese; Marco Righini; Lucia Lesa; Anna De Odorico; Elisa Bastiani; Stefania Pascut; Stefano Miceli; Silvio Brusaferro (Elsevier, 2022)
Objectives: What is the state of sexual and reproductive health (SRH) knowledge among teens? What about adolescents' attitudes toward SRH and the available supporting network? Study design: A cross-sectional study conducted between April and May 2018. Methods: An anonymous 36-item questionnaire on SRH knowledge, behaviors, and networks was developed, revised and validated by a multidisciplinary health professional team, then distributed to high school students in Udine (Italy). Results: 747 questionnaires were collected in five high schools; respondents were predominantly male, mean age 14.8 years; 48% of students have sufficient SRH knowledge (considered as above the mean value). Factors associated with higher knowledge levels were female sex, age, SES according to father's profession, first SRH information at age 11-13, Italy as country of origin, and attendance at a technical school. Conclusions: Students' knowledge on SHR resulted relatively poor. Sex, school type and previous experience of sexuality education were the most important factor associated with SRH knowledge.